THEORETICAL AND ORGANIZATIONAL FOUNDATIONS OF THE ORGANIZATION OF FINANCIAL CONTROL IN THE PUBLIC SECTOR (Conferencea, 2023)
This article is devoted to the theoretical and organizational foundations of the organization of financial control in the public sector.